PENGARUH SENAM IRAMA TERHADAP PENINGKATAN KECERDASAN KINESTETIK ANAK KELOMPOK B (STUDI EKSPERIMEN DI TK NEGERI PEMBINA CAKRANEGARA) TAHUN AJARAN 2024/2025 - Ni Luh Dwi Ayu Madya, Elisabeth; Habibi, Muazar; Nurhasanah, Nurhasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine the effect of rhythmic gymnastics on the improving of kinesthetic intelligence in Group B children at TK Negeri Pembina Cakranegara. The type of research use is quantitative research with the experimental research method. The population consisted of all students at TK Negeri Pembina Cakranegara, totaling 43 students, with 19 students in Group B. The sampling technique used in this study was saturated sampling, with a total of 19 students. Data collection techniques using treatment, pre-test and post-test. Data analysis was conducted using the t-test. The results of the study showed a significance value (2-tailed) of 0.000 < 0.05, indicating a significant difference between the pre-test and post-test scores. This proves that rhythmic gymnastics has an effect on the kinesthetic intelligence of children aged 5–6 years at TK Negeri Pembina Cakranegara. Therefore, it can be concluded that Ho is rejected and Ha is accepted, meaning that rhythmic gymnastics has an effect on the kinesthetic intelligence of children aged 5-6 years at TK Negeri Pembina Cakranegara.